How to deal with future uncertainty? An empirical study of undergraduates based on the theory of motivation information management - Feng, Zhuowen; Guo, Chuyu; Wang, Guancheng; Mo, Chunyan (Frontiers in Psychology, 2025)
Based on the Theory of Motivated Information Management (TMIM), this study examines how undergraduates manage information related to post-graduation pathways, with a particular focus on their interactions with teachers, family, and friends. In addition, it explores how individuals perceive and process information in uncertain situations, specifically examining undergraduates' behaviors and decision-making regarding employment and further education. Furthermore, this study sheds light on the decision-making processes of students facing graduation choices, particularly in terms of information management. It addresses a gap in the application of the TMIM model within the context of college graduation anxiety research, assessing its suitability as a decision-making model for information seeking related to graduation anxiety. The findings demonstrate the effectiveness of the TMIM framework in predicting information-seeking strategies, thereby supporting various application scenarios of information-seeking models for undergraduates.